Atogepant – an orally-administered CGRP antagonist – attenuates activation of meningeal nociceptors by CSD. (August 2022) - Strassman, Andrew M; Melo-Carrillo, Agustin; Houle, Timothy T; Adams, Aubrey; Brin, Mitchell F; Burstein, Rami
Background: This study investigated the mechanism of action of atogepant, a small-molecule CGRP receptor antagonist recently approved for the preventive treatment of episodic migraine, by assessing its effect on activation of mechanosensitive C- and Aδ-meningeal nociceptors following cortical spreading depression. Methods: Single-unit recordings of trigeminal ganglion neurons (32 Aδ and 20 C-fibers) innervating the dura was used to document effects of orally administered atogepant (5 mg/kg) or vehicle on cortical spreading depression-induced activation in anesthetized male rats. Results: Bayesian analysis of time effects found that atogepant did not completely prevent the activation of nociceptors at the tested dose, but it significantly reduced response amplitude and probability of response in both the C- and the Aδ-fibers at different time intervals following cortical spreading depression induction. For C-fibers, the reduction in responses was significant in the early phase (first hour), but not delayed phase of activation, whereas in Aδ-fibers, significant reduction in activation was apparent in the delayed phase (second and third hours) but not early phase of activation. Conclusions: These findings identify differences between the actions of atogepant, a small molecule CGRP antagonist (partially inhibiting both Aδ and C-fibers) and those found previously for fremanezumab, a CGRP-targeted antibody (inhibiting Aδ fibers only) and onabotulinumtoxinA (inhibiting C-fibers only)- suggesting that these agents differ in their mechanisms for the preventive treatment of migraine.